1994
DOI: 10.1021/ja00094a075
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Coordinatively Unsaturated Cp*Ir-Amino Acid Complexes and Their Highly Diastereoselective Complexation Reactions

Abstract: Amino acid-metal complexes have been the subject of innumerable studies,1 prompted by the roles of metals in biochem-istry2 and amino acids in producing chiral catalysts.3 With very few exceptions,4 amino acid-metal complexes are coordinatively* saturated. For example, interaction of -unsubstituted amino acid salts with [Cp*IrCl(M-Cl)]21 leads to 18-electron complexes 2, the stereogenic element of the amino acid producing mixtures modestly enriched in diastereomer 2a (from 50:50 up to 92:8).5 Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…[22,23,[36][37][38][39][40] All complexes adopt the three-legged piano-stool (half-sandwich) configuration, as expected. As is the case with Cp ⁄ Ir amino acid complexes previously reported, the iridium atom becomes a pseudo-tetrahedral chiral center upon coordination of the amino acid, resulting in diastereomers that differ at configuration of the metal when using an enantiomerically pure amino acid.…”
Section: Synthesis Of Amino Acid Complexessupporting
confidence: 76%
“…[22,23,[36][37][38][39][40] All complexes adopt the three-legged piano-stool (half-sandwich) configuration, as expected. As is the case with Cp ⁄ Ir amino acid complexes previously reported, the iridium atom becomes a pseudo-tetrahedral chiral center upon coordination of the amino acid, resulting in diastereomers that differ at configuration of the metal when using an enantiomerically pure amino acid.…”
Section: Synthesis Of Amino Acid Complexessupporting
confidence: 76%
“…This instability is likely why these ligand motifs are observed less frequently. Complexes of 3b, or the analogous bridging dimetal complex, have been reported for many metals (22,35,36), but the chelate ligand (3c) is the most commonly reported binding motif and has been reported or inferred for amino acids complexed with gold, nickel, zinc, copper, cobalt, iron, rhenium, molybdenum, ruthenium, rhodium, platinum, iridium, and tungsten (22,28,29,(37)(38)(39)(40). The N,O chelate complexes have been shown to be sensitive to the presence of better ligands, resulting in ligand swapping or degradation, suggesting weak coordination (29).…”
Section: Direct Amino Acid Attachmentmentioning
confidence: 99%
“…However many of the complexes have additional stabilization such as a third ligation point within the ligand (42,43) or non natural amino acids providing rigidity or electronic stability in the molecule (38,44,45). Ligation through more than two sites on the amino acids has also been reviewed (39,46,47).…”
Section: Direct Amino Acid Attachmentmentioning
confidence: 99%
“…[35] Both molecular and heterogenized WOCs exhibited remarkable activity; importantly, structural and reactivity studies revealed, not unexpectedly, that IrÀ OP(O)(OH)R bond is significantly weaker than IrÀ OC(O)R one. This suggested that having a mixed terdentate dianionic O(P),N,(C)O-ligand [68] could be ideal since the phosphonate arm could easily dissociate and act as anchoring moiety, whereas the amino acidate (AA) fragment could remain tightly bound at iridium, [69][70][71][72][73][74] stabilizing the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The search for ligands with such features straightly pointed toward glyphosate [N-(phosphonomethyl)glycine], a very controversial systemic herbicide and crop desiccant, [75][76][77] and its further methyl-phosphonated analogue glyphosine [N,N-bis (phosphonomethyl)glycine] (Scheme 1). Despite many Ir(AA)complexes have been reported [69][70][71][72][73][74] and successfully applied as catalysts [78][79][80][81][82][83][84] and anticancer agents, [85] to best of our knowledge, none of them bears coordinated glyphosate and glyphosine ligands. The transition metal coordination chemistry of these two molecules is, indeed, rather limited.…”
Section: Introductionmentioning
confidence: 99%